Microorganisms causing respiratory diseases in children in relation to age and diagnosis - Isaieva, H. O.; Mishyna, M. M.; Gonchar, M. O.; Logvinova, O. L.; Basiuk, M. A. (Regulatory Mechanisms in Biosystems, 2020)
Community-acquired pneumonia (CAP) in children is still one of the leading causes of morbidity and mortality, especially in developing countries. The World Health Organization (WHO) has reported that pneumonia accounts for 15% of all deaths of children under 5 years old. The aim of the present study was to find out the predominance of microorganisms in the respiratory tract in children. 334 strains of microorganisms were isolated: Gram-positive – 293 strains, Gram-negative – 41. From the pharynx 183 strains were isolated, from the nose – 94, from sputum – 57. Among Gram-positive microorganisms the following were isolated: Staphylococcus aureus 44 strains of microorganisms, S. epidermidis – 75, Group A β-hemolytic streptococci – 39, viridans streptococci – 55, Streptococcus pneumoniae – 34, Enterococcus faecalis – 2, Candida spp. – 38, Corynebacterium pseudodiphthericum – 6. Among Gram-negative microorganisms the following were isolated: Escherichia coli 4 strains of microorganisms, Klebsiella pneumoniae – 13, Pseudomonas aeruginosa – 6, Haemophilus influenzae – 11, Enterobacter cloacae – 7. Children were divided by age and diagnosis into four groups: I group – children with acute bronchitis (0–5 years of age), II group – children with acute bronchitis (5–18 years of age), III group – children with CAP (0–5 years of age), IV group – children with CAP (5–18 years of age). Materials used in the research – nasal swabs, throat swabs and sputum. Microorganisms were isolated and identified using standard microbiological methods. S. aureus was the predominant microorganism isolate from the pharynx in children with bronchitis (0–5 years). Group A β-hemolytic streptococci were isolated most often from the pharynx in children with bronchitis older than 5 years and in children with CAP less than 5 years of age. S. pneumoniae was most often isolated from the pharynx in children older than 5 years of age with CAP. S. aureus was the main microorganism, isolated from the nose in children with bronchitis in all age groups; in patients with CAP it was the predominant microorganism in children older than 5 years of age. S. aureus was the predominant microorganism, isolated from sputum in children with bronchitis older than 5 years. S. pneumoniae was the predominant microorganism, isolated from sputum in children with CAP older than 5 years. The research showed that S. pneumoniae is still one of the main pathogens that cause CAP in school aged children.